Laminin-1 Peptides Conjugated to Fibrin Hydrogels Promote Salivary Gland Regeneration in Irradiated Mouse Submandibular Glands - Nam, Kihoon; dos Santos, Harim T.; Maslow, Frank; Trump, Bryan G.; Lei, Pedro; Andreadis, Stelios T.; Baker, Olga J. (Frontiers in Bioengineering and Biotechnology, 2021)
Previous studies demonstrated that salivary gland morphogenesis and differentiation are enhanced by modification of fibrin hydrogels chemically conjugated to Laminin-1 peptides. Specifically, Laminin-1 peptides (A99: CGGALRGDN-amide and YIGSR: CGGADPGYIGSRGAA-amide) chemically conjugated to fibrin promoted formation of newly organized salivary epithelium both in vitro (e.g., using organoids) and in vivo (e.g., in a wounded mouse model). While these studies were successful, the model’s usefulness for inducing regenerative patterns after radiation therapy remains unknown. Therefore, the goal of the current study was to determine whether transdermal injection with the Laminin-1 peptides A99 and YIGSR chemically conjugated to fibrin hydrogels promotes tissue regeneration in irradiated salivary glands. Results indicate that A99 and YIGSR chemically conjugated to fibrin hydrogels promote formation of functional salivary tissue when transdermally injected to irradiated salivary glands. In contrast, when left untreated, irradiated salivary glands display a loss in structure and functionality. Together, these studies indicate that fibrin hydrogel-based implantable scaffolds containing Laminin-1 peptides promote secretory function of irradiated salivary glands.